2020
DOI: 10.1371/journal.pone.0239979
|View full text |Cite
|
Sign up to set email alerts
|

Neuron-specific enolase and neuroimaging for prognostication after cardiac arrest treated with targeted temperature management

Abstract: Background Prognostication after cardiac arrest (CA) needs a multimodal approach, but the optimal method is not known. We tested the hypothesis that the combination of neuron-specific enolase (NSE) and neuroimaging could improve outcome prediction after CA treated with targeted temperature management (TTM). Methods A retrospective observational cohort study was performed on patients who underwent at least one NSE measurement between 48 and 72 hr; received both a brain computed tomography (CT) scan within 24 hr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Serum NSE levels are higher in patients with ischemic stroke than in healthy controls and correlate with infarct size and neurological deficits [17,18]. Several studies have demonstrated the prognostic significance of serum NSE concentrations in ischemic [17,[19][20][21][22][23] and hemorrhagic stroke [24], hypertension [25,26], ischemia-reperfusion brain injury [27], and out-of-hospital cardiac arrest [28][29][30][31]. Based on these findings, the American Academy of Neurology recommended the use of serum NSE to predict adverse outcomes after global cerebral hypoperfusion in patients requiring cardiopulmonary resuscitation [32].…”
Section: Introductionmentioning
confidence: 99%
“…Serum NSE levels are higher in patients with ischemic stroke than in healthy controls and correlate with infarct size and neurological deficits [17,18]. Several studies have demonstrated the prognostic significance of serum NSE concentrations in ischemic [17,[19][20][21][22][23] and hemorrhagic stroke [24], hypertension [25,26], ischemia-reperfusion brain injury [27], and out-of-hospital cardiac arrest [28][29][30][31]. Based on these findings, the American Academy of Neurology recommended the use of serum NSE to predict adverse outcomes after global cerebral hypoperfusion in patients requiring cardiopulmonary resuscitation [32].…”
Section: Introductionmentioning
confidence: 99%